Portrait of Good EFL Thesis Advisors - Saiful Saiful (Proceedings of AICS - Social Sciences, 2017)
This study aimed to reveal characteristics of good EFL thesis advisors in the forms of students’ opinions in association with two research variables namely adequacy of English proficiency and adequacy of content knowledge. The study employs qualitative approach which is intended to develop and build a theory about EFL thesis advisor effectiveness by means of grounded theory method. The data were obtained from 15 EFL graduate students through in-depth interview. The obtained data were analyzed by using three techniques namely open coding, axial coding, and selective coding. From the respondents’ accounts, the results showed that good thesis advisors should have good technical knowledge consisting of two main qualities namely adequacy of English proficiency and adequacy of content knowledge. To conclude, good EFL thesis advisors must be at advanced level of English language skills and have good ability of appropriate content knowledge covering English grammar, syntax, linguistic, phonology, language and culture, sociolinguistics, psycholinguistics, error analysis and discourse analysis. Keywords: EFL thesis advisors, English proficiency, content knowledge.